Analisis Fundamental dan Teknikal Saham pada PT Astra International Tbk Tahun 2022-2023 - Saputra, Ananda; Haryono, Haryono; Zul Azmi (WANARGI : Jurnal Manajemen Dan Akuntansi, 2025)
This study evaluates the performance of PT Astra International Tbk. (ASII) stock during 2021-2023 through fundamental and technical analysis. The results show that ASII recorded a net profit of IDR 33.8 trillion in 2023, growing by 16.91% YoY, with main revenues derived from the heavy equipment, mining, and automotive sectors. The consistent increase in Earnings Per Share (EPS) and the decline in the Price to Earnings Ratio (PER) indicate increasingly attractive stock valuations, while the Debt to Equity Ratio (DER) remains under control. Technical analysis using the Stochastic Oscillator, MACD, and SMA indicators reveals buying and selling opportunities with price trends shifting from bullish to bearish. In conclusion, ASII stock holds promising prospects, supported by strong financial performance and a commitment to sustainability